An Error Analysis on The Use of Simple Past Tense in Narrative Text in Mts Jawharot Al Muzakky - budik kusworo; Hamdan Zulva (English Language Teaching Journal, 2026)
English is crucial in Indonesia's educational curriculum, taught early to ensure proficiency by graduation. Its global importance is seen in business, technology, science, and tourism. Mastering English, especially tenses like the Simple Past Tense, is key for effective communication. However, many students struggle with its rules and structure. This study aims to analyze these errors in narrative texts, providing insights and recommendations to improve English education at Jawharot Al Muzakky Islamic Junior High School in Malang. Using descriptive qualitative methods, the authors explored error patterns in the simple past tense among Class 9C students at MTS Jawharot Al Muzakky. Observations, interviews, and analysis of students' written work revealed common mistakes such as omitting the -ed ending on regular verbs and incorrect forms of irregular verbs. These insights can help teachers develop effective strategies to improve student learning and understanding of grammar. The assessment instrument evaluates students' narrative writing using the simple past tense, focusing on grammar, discourse management, punctuation, and neatness, rated on a scale of 1 to 4. Grammar and vocabulary scored 68.75%, indicating moderate difficulty. Discourse management scored 65.63%, showing partial relevance in idea processing. Punctuation use scored 56.25%, with 50% errors. Neatness scored 69.75%, indicating legible but untidy writing. The results suggest students have basic proficiency but need improvement in these areas.